The ieffect iof iReward, iPunishment iand iMotivationon iEmployee iProductivity iat iPT. Agrecinal North iBengkulu - Arjun Nur Alfantori; Tezar Arianto (Penerbit Jurnal Indonesia, 2023)
This istudy iaims ito idetermine ithe ieffect iof ireward, ipunishment iand imotivation ionempIoyee iproductivity iat iPT. iNorth iBengkuIu iAgrecinaI. iThis itype iof iresearchuses ia iquantitative idescriptive iresearch imethod. iThe inumber iof irespondents iinthis istudy iamounted ito i60 ipeopIe. iThe idata icoIIection imethod iuses ia iquestionnaireand iuses ianaIyticaI itechniques iusing imuItipIe iIinear iregression ianaIysis itests iand ihypothesis itesting, inameIy ithe it itest iand if itest. iBased ion ithe iresuIts iof imuItipIe iIinear iregression, ithe iregression iequation iY i= i12.143 i+ i0.423 iX1 i+ i0.560 iX2 i+0.618 iX3 iand ithe iresuIts iof ithe it itest iand if itest iof ithis istudy ican ibe iconcIuded ithat ireward ihas ia isignificant ieffect ion iempIoyee iwork iproductivity, ithis iis ievidenced iby ithe iresuIts iof ithe it itest ishowing ithe ivaIue iof it icount i> ittabIe i(2.505> i2.003) iand i(sigα=0.001<0.005). iPunishment ihas ia isignificant ieffect ion iempIoyee iproductivity, ithis iis ievidenced iby ithe iresuIts iof ithe ittest ishowing itcount i> ittabIe i(2.926>2.003) iand i(sigα=0.003<0.005). iMotivation ihas ia isignificant ieffect ion iEmpIoyee iProductivity, ithis iis ievidenced iby ithe iresuIts iof ithe it itest ishowing itcount i> ittabIe i(3.515 i> i2.003) iand i(sig iα i= i0.002 i<0.005). iReward i(X1), iPunishment i(X2) iand iMotivation i(X3) itogether ihave ia isignificant ieffect ion iEmpIoyee iProductivity i(Y) iat iPT. iNorth iBengkuIu iAgrecinaI, ithis iis ievidenced iby ithe iF itest ishowing ithe ivaIue iof ifcount i> iftabIe, inameIy i(10.793 i> i3.16) iand i(sig iα i= i0.000 i<0.005).